GPR139 agonist and antagonist differentially regulate retrieval and consolidation of fear memory in the zebrafish - Roy, Nisa; Ogawa, Satoshi; Tsuda, Sachiko; Parhar, Ishwar S. (Frontiers in Neuroscience, 2024)
G protein-coupled receptor 139 (GPR139), a highly conserved orphan receptor, is predominantly expressed in the habenula of vertebrate species. Habenula is an ancient epithalamic structure, which is critical to comprehending adaptive behaviors in vertebrates. We have previously demonstrated the role of GPR139 agonists in fear-associated decision-making processes in zebrafish. However, how GPR139 signaling in the habenula modulates such adaptive behavioral responses remains unsolved. Fish centrally administered with a synthetic antagonist for human GPR139 (NCRW0005-F05) exhibited significant suppression of odorant cue (alarm substance, AS)-induced fear learning in the conditioned place avoidance paradigm. On the other hand, co-treatment with a GPR139 antagonist and a synthetic agonist for human GPR139 (JNJ-63533054) interrupted the fear conditioning process by significantly reducing locomotion during post-conditioning. Calcium imaging of acute brain slices showed a significant increase in peak amplitude of calcium transients in the habenula upon bath application of either a GPR139 antagonist or agonist. Furthermore, KCl-evoked calcium transients were reduced by the GPR139 antagonist and co-treatment of the GPR139 antagonist–agonist. These results suggest that the GPR139 antagonist did not block the inhibitory action of the GPR139 agonist in the decision-making process during the fear-retrieval phase; however, solitarily, it functions in governing the fear consolidation process via activation of the ventral habenula neurons in zebrafish.